GRASSROOTS INNOVATION AND RURAL ENTREPRENEURSHIP IN INDIA: A PATHWAY TO INCLUSIVE AND SUSTAINABLE GROWTH - Suresh Reddy Jakka (International Journal of Advances in Business and Management Research (IJABMR), 2025)
India’s rural economy remains a foundational pillar of national development, yet it continues to struggle with deep-rooted issues such as poverty, underemployment, and socio-economic exclusion. Grassroots innovation and rural entrepreneurship have emerged as pivotal mechanisms to confront these challenges by harnessing indigenous knowledge and encouraging local enterprise. This paper analyses the conceptual underpinnings, policy environment, and practical outcomes of grassroots innovation and rural entrepreneurship in India. It incorporates literature reviews, statistical insights, and illustrative case studies to examine how these approaches contribute to a more inclusive and sustainable growth model. The paper concludes with strategic recommendations to enhance institutional frameworks and scale successful initiatives across varied rural settings.